Genomic Analysis of SARS-CoV-2 in Libya: Spatiotemporal Clade Dynamics and Mutations Influencing Viral Virulence - Wafa Elmghirbi,; Mohamed Lazhari,; Mawada Elside,; Mabroka Alghros,; Samia Alzentani,; Omran Algriany, (AlQalam Journal of Medical and Applied Sciences, 2026)
The ongoing evolution of SARS-CoV-2 has resulted in emerging variants with increased transmissibility and immune escape. In order to strengthen studies on pandemic evolution and set the public health responses, the incorporation of genomic data from global databases such as NCBI and bioinformatics platforms, e.g., Nextclade, has played an important role. This retrospective study was conducted to investigate the genomic diversity among SARS-CoV-2 sequences in Libya from March 2020 to December 2022, through assigning variant distribution and key mutations with the possible functional implications. Eighty-one (81) high-quality SARS-CoV-2 genomes from Libya were retrieved from NCBI, of which thirty (30) sequences were then analyzed for clade assignment, quality assessment, and mutational profiles. SARS-CoV-2 sequences were classified into lineages by using Pangolin software (V4.x.). All 30 sequences had high quality with minimal sequencing errors. Clade distribution results showed that the dominant variants were 21D (Eta) and 22B (Omicron BA.5) at 50% and 20%, respectively. Other detected sublinages were 21L (16.7%), 22C (10%), 20B (B.1.1, 3.3%), 19B (3.3%). The major nucleotide mutations in clade 21D included C241T (5' UTR; 100%) and C884T (ORF1ab; 93%), and in 22B T670G (ORF1ab; 100%) and C1627T (ORF1ab; 83%). Moreover, the amino acid substitutions included S: E484K (100%) in 21D, S: F486V (100%) in 22B, ORF1ab: P314L (100%) in 21L, and S: D614G (100%) in 22C. Our findings identified a complex genetic diversity in SARS-CoV-2 variants in Libya, which carried important mutational changes, and underscored the increased need for continuous and large-scale sequencing analysis to understand the local and international trajectory of the pandemic.